2015
DOI: 10.1039/c5dt01829c
|View full text |Cite
|
Sign up to set email alerts
|

Thermochromism and switchable paramagnetism of cobalt(ii) in thiocyanate ionic liquids

Abstract: Temperature-dependent switching of paramagnetism of a cobalt(II) complex is observed in an ionic liquid solution. Paramagnetic and thermochromic switching occur simultaneously due to a reversible change in coordination. This reversible switching is possible in the ionic liquid solution, which enables mobility of thiocyanate anions by remaining mobile at low temperatures and acts as an anion reservoir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 22 publications
4
52
0
Order By: Relevance
“…Transition metals such as Co, Zn and many others have also been used to obtain metal-containing ionic liquids. [12][13][14] Lin et al have reviewed some of these metal-containing ILs with imidazolium used as cation. 15 Another example of metalcontaining ionic liquids are deep-eutectic-solvents with metals incorporated as anions or cations, firstly introduced by Abbott et al 16 Yoshida et al iron-containing magnetic ionic liquids, which are good examples of these materials adding additional intrinsic properties such as magnetism.…”
mentioning
confidence: 99%
“…Transition metals such as Co, Zn and many others have also been used to obtain metal-containing ionic liquids. [12][13][14] Lin et al have reviewed some of these metal-containing ILs with imidazolium used as cation. 15 Another example of metalcontaining ionic liquids are deep-eutectic-solvents with metals incorporated as anions or cations, firstly introduced by Abbott et al 16 Yoshida et al iron-containing magnetic ionic liquids, which are good examples of these materials adding additional intrinsic properties such as magnetism.…”
mentioning
confidence: 99%
“…We thus extend our reaction studies to a metal-ligand complex reaction under thermodynamic equilibrium conditions. 108 For this purpose, XPS was applied to the dynamical metal complex system based on an IL with the doubly negatively charged [Co(II) (NCS) 4 ] 2 as anion; 126 for this anion, Osborne et al 127 reported a thermochromatic transformation to the doubly negatively charged [Co(II) (NCS) 6 ] 4 anion upon cooling. The scheme of the corresponding complex equilibrium is depicted in Scheme 6.…”
Section: Liquid-liquid Reactions: Thermochromic Transformation Ofmentioning
confidence: 99%
“…At room temperature, the equilibrium lies on the left hand side, as witnessed by the deep blue colour of the tetrahedrally coordinated cobalt anion. Cooling shifts the equilibrium to the right, as evident from the red colour of the octahedrally coordinated complex at around 40 • C. 127 In order to elucidate the dynamical behavior, we studied a mixture of the IL di SCN] ). Notably, the latter has an excess of one IL-1 ion pair per formed octahedral complex.…”
Section: Liquid-liquid Reactions: Thermochromic Transformation Ofmentioning
confidence: 99%
“…Herein, we apply XPS for the first time to a thermodynamic metal complex equilibrium based on ILs containing the doubly negatively charged tetrathiocyanatocobaltate(II) ([Co(NCS) 4 ] 2– ) as the anion, a system introduced by Peppel et al 16 Osborne et al 17 reported thermochromatic behavior of this anion formed by dissolving cobalt(II) isothiocyanate (Co(NCS) 2 ) in the IL 1-ethyl-3-methylimidazolium thiocyanate ([C 2 C 1 Im][SCN]). At room temperature, the complex equilibrium in Scheme 1 lies on the left side, as witnessed by the deep blue color of the tetrahedrally coordinated cobalt anion.…”
mentioning
confidence: 99%
“…Cooling shifts the equilibrium to the right, toward the octahedrally coordinated complex: At around −40 °C, the octahedral red form in the bulk dominates, as shown by UV–vis and IR absorption spectroscopy. 17 It should be noted that the transition between both complexes goes not only along with changes in optical absorption but also with changes in magnetic properties 17 and conductivity. 18 Very recently, it was also demonstrated that the equilibrium is shifted to the right by applying external pressure.…”
mentioning
confidence: 99%